Efforts To Improve Learning Achievement Of 8th Grade Students In SMPN 9 Sorong Through The Application Of Problem Solving Type Cooperative Learning Models In Christian Religious Education Subjects - Tamaela, Ellen (Sains Global Institut, 2019)
This research is a classroom action research that aims to see whether there is an influence on the application of problem solving learning models in an effort to improve PAK learning achievement. The subjects in this study were selected from students of class VIII-2 SMPN 9 Sorong City in the 2018/2019 academic year with a total of 25 students. The research procedure is a series of stages of research from beginning to end. This CAR procedure consists of 2 cycles. Each cycle consists of four stages as follows: 1) planning; 2) implementing actions; 3) observation and evaluation of actions; and 4) reflection of actions. Research data were collected using interviews, observations, and tests. The data of this study were analyzed using data analysis techniques as follows; (1) Comparative analysis is done by comparing the results obtained in the first cycle with the second cycle and; (2) Qualitative Analysis in the form of field notes which are presented in detail and in full throughout the research process. This research is said to be successful if in learning students get a minimum of 75% of the number of students already active in the learning process and a minimum of 75% student achievement increases. The results of the study show that: (1) based on the results of research observations, it can be concluded that the application of the problem solving learning model can increase student activity during learning. This is indicated by a change in students' attitudes in learning, including the interaction and cooperation between students the better, the more students have the courage to express ideas and opinions in front of the class. The center of learning is no longer on the teacher. Students are required to actively search for information and must be able to exchange ideas; (2) based on data in the form of pre-observation values ??and after research, it can be concluded that the application of problem solving learning models can improve student learning achievement.